Răspuns :
2 x ( x + 1) - 3 ( x + 1) = 2 x² + 2 x - 3 x - 3 = 2 x² - x - 3
sau dai factor comun: ( x + 1) ( 2 x - 3)
5 (x - 1 ) + 1 x (x-1) = 5 x - 5 + x² - x = x² + 4 x - 5
sau factor comun: ( x-1)(5 +x)
8 x ( 2 x + 1) - 4 ( 2 x + 1) = 16 x² + 8 x - 8 x - 4 = 16 x² - 4 = 4 ( 4 x² - 1) =
= 4( 2x-1)(2x+1)
sau factor comun: 4(2x+1)(2x-1)
sau dai factor comun: ( x + 1) ( 2 x - 3)
5 (x - 1 ) + 1 x (x-1) = 5 x - 5 + x² - x = x² + 4 x - 5
sau factor comun: ( x-1)(5 +x)
8 x ( 2 x + 1) - 4 ( 2 x + 1) = 16 x² + 8 x - 8 x - 4 = 16 x² - 4 = 4 ( 4 x² - 1) =
= 4( 2x-1)(2x+1)
sau factor comun: 4(2x+1)(2x-1)